Monitoring Hypocoagulant Conditions in Rat Plasma: Factors Determining the Endogenous Thrombin Potential of Tissue Factor-Activated Plasma - Nieuwenhuys, Cécile M. A.; Feijge, Marion A. H.; Béguin, Suzette; Heemskerk, Johan W. M. (Thrombosis and Haemostasis, 2000)
Automated human plasma, continuous monitoring of the formation and inactivation of thrombin during the coagulation process provides an adequate way to detect hypo- and hypercoagulant conditions. Here, we describe an analogous procedure to determine the endogenous thrombin potential (ETP), i. e. the free thrombin concentration-time integral, of coagulating rat plasma. When activated with tissue factor, the ETP of plasma from Wistar rats was comparable to the ETP of human plasma, in spite of a relatively short half-life time of free thrombin in rat plasma. The ETP was highly sensitive to heparin as well as to administration of vitamin K antagonist or feeding of the animals with a vitamin K-deficient diet. In plasma that was activated under sub-optimal conditions (reduced levels of tissue factor or vitamin K-dependent coagulation factors), the ETP increased with the rate of thrombin formation in the first minutes of the coagulation process. Since both parameters are dependent of the prothrombin concentration, it appears that this level plays an important role in determining both the initial and total activity of the coagulation system. Thus, automated measurement of free thrombin during the coagulation process of rat plasma allows a detailed analysis of hypocoagulability in this animal model.
Keywords: Endogenous thrombin potential; hypocoagulability; rat; tissue factor; vitamin K